Estrogenic effects of herbal medicines from Costa Rica used for the management of menopausal symptoms - Pérez Sánchez, Alice Lorena (2009)
Objective: Outcomes from the Women's Health Initiative have demonstrated adverse effects associated with hormone therapy and have prioritized the need to develop new alternative treatments for the management of menopause and osteoporosis. To this end, we have been investigating natural herbal medicines used by Costa Rican women to manage menopausal symptoms. Methods: Seventeen plant species were collected and extracted in Costa Rica. To establish possible mechanisms of action and to determine their potential future use for menopause or osteoporosis, we investigated the estrogenic activities of the herbal extracts in an estrogen-reporter gene estrogen receptor (ER) β-Chemically Activated Luciferase Expression assay in U2-OS cells and in reporter and endogenous gene assays in MCF-7 cells. Results: Six of the plant extracts bound to the ERs. Four of the six extracts stimulated reporter gene expression in the ER-β-Chemically Activated Luciferase Expression assay. All six extracts modulated expression of endogenous genes in MCF-7 cells, with four extracts acting as estrogen agonists and two extracts, Pimenta dioica and Smilax domingensis, acting as partial agonist/antagonists by enhancing estradiol-stimulated pS2 mRNA expression but reducing estradiol-stimulated PR and PTGES mRNA expression. Both P. dioica and S. domingensis induced a 2ERE-luciferase reporter gene in transient transfected MCF-7 cells, which was inhibited by the ER antagonist ICI 182,780. Conclusions: This work presents a plausible mechanism of action for many of the herbal medicines used by Costa Rican women to treat menopausal symptoms. However, it further suggests that studies of safety and efficacy are needed before these herbs should be used as alternative therapies to hormone therapy.